Gonadotropin Releasing Hormone Agonis (GNRH-A) vs Human Chorionic Gonadotropin (hCG) vs Gonadotropin Releasing Hormone Agonis (GNRH-A) + Human Chorionic Gonadotropin (HCG) sebagai stimulan pematangan oosit, tingkat pembuahan, kualitas embrio, tingkat keha - Putu Nody Asta Kusuma; Jaqueline Sudirman; Made Suyasa Jaya; I Gede Ngurah Harry Wijaya Surya; Anak Agung Ngurah Anantasika; Ida Bagus Putra Adnyana (Intisari Sains Medis, 2021)
Background: The stimulation of Human Chorionic Gonadotropin (hCG) vs. Gonadotropin-Releasing Hormone (GnRH) agonists vs. hCG + GnRH agonists plays an important role in influencing oocyte maturation, fertilization, embryo quality, pregnancy, live birth rates, and Ovarian Hyperstimulation Syndrome (OHSS) during IVF. This study aims to determine the effectiveness of hCG vs. GnRH agonist stimulation vs. hCG + GnRH agonists regarding oocyte maturation levels, embryo quality, fertilization, pregnancy, live birth rates, and OHSS while undergoing IVF program.Methods: This cross-sectional analytic study was conducted on 86 samples, including 33 hCG group, 12 GnRH agonist group, and 41 hCG + GnRH agonist group. The secondary data was obtained from the IVF clinical laboratory results at Puri Bunda Hospital and BROS hospital. Data were analyzed using SPSS version 20 for Windows.Results: There were no significant differences in age, duration of infertility, levels of Follicle Stimulating Hormone (FSH), Luteinizing Hormone (LH), estradiol, duration of stimulation, level of oocyte maturation, fertilization, embryo quality, pregnancy, live birth rate and OHSS ( p> 0.05) in each group. However, there was a significant difference in the Body Mass Index (BMI) (p = 0.032) and the number of oocytes (p = 0.020) in each group.Conclusion: There were no significant differences in oocyte maturation, fertilization rates, embryo quality, pregnancy, live birth rates, and OHSS.  Latar Belakang: Stimulasi Human Chorionic Gonadotropin (hCG) vs Gonadotropin Releasing Hormone (GnRH) agonis vs hCG+GnRH agonis berperan penting dalam mempengaruhi pematangan oosit, pembuahan, kualitas embrio, kehamilan, tingkat kelahiran hidup, dan Ovarian Hiperstimulation Syndrome (OHSS) pada saat menjalani program bayi tabung. Penelitian ini bertujuan untuk mengetahui efektifitas dari stimulasi hCG vs GnRH agonis vs hCG+GnRH agonis mengenai tingkat pematangan oosit, kualitas embrio, pembuahan, kehamilan, kelahiran dan OHSS saat menjalani program bayi tabung.Metode: Penelitian potong lintang analitik ini dilakukan terhadap 86 sampel meliputi 33 kelompok hCG, 12 kelompok GnRH agonis, dan 41 kelompok hCG+GnRH agonis. Data sekunder diperoleh dari hasil laboratorium klinik IVF Rumah Sakit Puri Bunda dan rumah sakit BROS. Data dianalisis dengan SPSS versi 20 untuk Windows.Hasil: Tidak terdapat perbedaan bermakna pada usia, durasi infertilitas, kadar Follicle Stimulating Hormone (FSH), Luteinizing Hormone (LH), estradiol, durasi stimulasi, tingkat pematangan oosit, pembuahan, kualitas embrio, kehamilan, tingkat kelahiran hidup dan OHSS (p>0,05) pada masing-masing kelompok. Namun, terdapat perbedaan bermakna pada Indeks Massa Tubuh (IMT) (p=0,032) dan jumlah oosit (p=0,020) pada masing-masing kelompok.Kesimpulan: Tidak ditemukannya perbedaan yang bermakna pada tingkat pematangan oosit, pembuahan, kualitas embrio, kehamilan, tingkat kelahiran hidup dan OHSS.